Biomass gasification in a fixed bed downdraft ractor with oxygen enriched air: A modified equilibrium modeling study - Poramate Sittisun (2019)
© 2019 The Authors. Published by Elsevier Ltd. Biomass conversion by gasification process is increasingly becoming attractive, especially for ceramic making industry, to transform biomass materials into combustible fuel gas called producer gas. This producer gas can then be used to fully or partially substitute liquefied petroleum gas in ceramic firing process. However, air gasification is known to generate low calorific value of gaseous fuel (3-6 MJ/Nm3) which may not be able to generate sufficiently high temperature (> 1200 oC) flame required by ceramic firing process. Use of oxygen enriched air is therefore of great interest if medium to high calorific value producer gas is required. In this work, a modified equilibrium model of global gasification reactions is developed to predict the resultant distribution of combustible gas species in the producer gas and to study the effect of operating parameters (oxygen content in air, and equivalence ratio) in a gasification process of agro-residues in a fixed bed downdraft gasifier at a fixed temperature. The modified equilibrium model of global gasification reactions developed in this work is based on thermodynamically stoichiometric approach due to its simplicity and reduced computational time. Model predictions of reaction kinetic constants for gasification reactions and gas concentration are validated by comparing with available experimental data. Simulation of influence of oxygen content in air (21-50%) and equivalence ratio (0.15-0.35) on composition of combustible gas and its heating value is carried out. The preliminary model simulation is found to give good qualitative prediction of experimental results. For maximum calorific value of producer gas generated, oxygen content in air should be 50%, and the equivalence ratio should be 0.15, respectively. For better accuracy of this modified equilibrium model, unconverted char and tar should be further considered.